2021
DOI: 10.1177/10497323211003067
|View full text |Cite
|
Sign up to set email alerts
|

“You Probably Won’t Notice Any Symptoms”: Blood Pressure in Pregnancy—Discourses of Contested Expertise in an Era of Self-Care and Responsibilization

Abstract: Pregnancy is not a disease or illness, but requires clinical surveillance as life-threatening complications can develop. Preeclampsia, one such potentially serious complication, puts both mother and baby at risk. Self-monitoring blood pressure in the general population is well established, and its potential in pregnancy is currently being explored. In the context of self-monitoring, the information and guidance given to women regarding hypertension, and the literature they themselves seek out during pregnancy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…One challenge concerns the increased 'responsibilisation' implied by remote care models. Those less fluent in participatory approaches to health, less able to exercise responsibility and self-efficacy [24][25][26][27] and lacking in socio-economic capital, including having a private space to take a call, a phone, and availability to be phoned, may be alienated or put at risk by the degree of responsibility they have to assume for their own antenatal health in remote appointments. Similarly, the use of digital resources described by some participants can help support understanding as to which symptoms require professional attention, but it requires 'digital work' that individuals are not equally able to undertake.…”
Section: Discussionmentioning
confidence: 99%
“…One challenge concerns the increased 'responsibilisation' implied by remote care models. Those less fluent in participatory approaches to health, less able to exercise responsibility and self-efficacy [24][25][26][27] and lacking in socio-economic capital, including having a private space to take a call, a phone, and availability to be phoned, may be alienated or put at risk by the degree of responsibility they have to assume for their own antenatal health in remote appointments. Similarly, the use of digital resources described by some participants can help support understanding as to which symptoms require professional attention, but it requires 'digital work' that individuals are not equally able to undertake.…”
Section: Discussionmentioning
confidence: 99%
“…The contrast between healthcare professionals and patients has also been highlighted in other research in the pregnant population. A discourse analysis of online, offline, and unofficial sources of information around pregnancy and high blood pressure also found a contradiction between the paternalistic discourse of clinicians and the lay discourse of women that both sought control [ 25 ]. Interestingly, despite clinicians concerns about passing control to women, few women reported not following advice while self-monitoring in our study, which corresponds to findings about telemonitoring of BP in the general population [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…In pregnancy, the sharing of lay knowledge and expertise is commonplace. Hinton et al demonstrated the nature of information sharing among pregnant people, often now in the form of online communities, in those with pregnancy hypertension or raised blood pressure 28. Pregnant women with hypertension valued the advice and support of their peers, and in the online space peer advice tended to trump the advice of medical professionals 28.…”
Section: Discussionmentioning
confidence: 99%
“…Hinton et al demonstrated the nature of information sharing among pregnant people, often now in the form of online communities, in those with pregnancy hypertension or raised blood pressure 28. Pregnant women with hypertension valued the advice and support of their peers, and in the online space peer advice tended to trump the advice of medical professionals 28. Support networks are a central part of any self-management model in the general population, often emphasising that ‘self-management is manifested as both an individual and family construct’ 27.…”
Section: Discussionmentioning
confidence: 99%